2019
DOI: 10.1016/j.physletb.2019.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Towards resolving the Λ3H lifetime puzzle

Abstract: Recent 3 Λ H lifetime measurements in relativistic heavy ion collision experiments have yielded values shorter by (30±8)% than the free Λ lifetime τ Λ , thereby questioning the naive expectation that τ ( 3 Λ H) ≈ τ Λ for a weakly bound Λ hyperon. Here we apply the closure approximation introduced by Dalitz and coworkers to evaluate the 3 Λ H lifetime, using 3 Λ H wavefunctions generated by solving three-body Faddeev equations. Our result, disregarding pion final-state interaction (FSI), is τ ( 3 Λ H)=(0.90±0.0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 41 publications
4
41
1
Order By: Relevance
“…However, the ALICE Collaboration [4] recently reported the result τ ( 3 H) = 237 +33 −36 ps, which is moderately closer to τ . This is one of the most topical issues to study in hypernuclear physics [5] and is essential because 3 H is the lightest hypernucleus which provides valuable information on interactions of a hyperon with nucleons [6]. In addition, the HypHI Collaboration [1] suggested that the lifetime of a 4 H hypernucleus, τ ( 4 H) = 140 +48 −33 ps, is shorter than the τ ( 4 H) = 194 +28 −26 ps measured in stopped K − experiments at KEK [7], whereas theoretical calculations [8,9] predicted τ ( 4 H) = 196-264 ps, which depends on the wave functions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ALICE Collaboration [4] recently reported the result τ ( 3 H) = 237 +33 −36 ps, which is moderately closer to τ . This is one of the most topical issues to study in hypernuclear physics [5] and is essential because 3 H is the lightest hypernucleus which provides valuable information on interactions of a hyperon with nucleons [6]. In addition, the HypHI Collaboration [1] suggested that the lifetime of a 4 H hypernucleus, τ ( 4 H) = 140 +48 −33 ps, is shorter than the τ ( 4 H) = 194 +28 −26 ps measured in stopped K − experiments at KEK [7], whereas theoretical calculations [8,9] predicted τ ( 4 H) = 196-264 ps, which depends on the wave functions.…”
Section: Introductionmentioning
confidence: 99%
“…Also shown in the figure are the τ calc ( 3 Λ H) values listed in Table 2, all of which are insufficiently short to reproduce the recently measured shorter lifetime values, except the very recent one by ALICE [56]. While enhancement of the free Λ decay rate by up to ≈20% is theoretically conceivable [48], it appears inconceivable to reproduce the 30% or so enhancement suggested by the recent heavy-ion experiments. [52], HypHI [53], ALICE [54], STAR [55] and ALICE [56].…”
Section: Charge Symmetry Breakingmentioning
confidence: 85%
“…[49]. The RD methodology was also used in the Congleton [46] and Gal-Garcilazo (GG) [48] calculations, with the latter one solving appropriate three-body Faddeev equations to produce a 3 Λ H wavefunction. The Kamada et al calculation [47], while also solving Faddeev equations for the 3 Λ H wavefunction, accounted microscopically for the outgoing 3N phase space and FSI, thereby doing without a closure approximation.…”
Section: Charge Symmetry Breakingmentioning
confidence: 99%
“…Therefore, the 3 Λ H can serve as an excellent experimental way to explore the Y N interaction. Recent precise lifetime measurements of 3 Λ H had been carried out in heavy-ion collisions [7,12,13], but the most precise measurements of the mass were made about 40 years ago [14][15][16][17][18] and they may suffer from a large systematic uncertainty [18,19]. The STAR detector [20][21][22] (the Solenoidal Tracker at RHIC) located in Brookhaven National Laboratory provides us an ideal playground to precisely measure the masses of 3 Λ H and its antimatter partner 3 Λ H [10].…”
Section: Introductionmentioning
confidence: 99%